2011
DOI: 10.1111/j.1465-7295.2011.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearities and the Sustainability of the Government's Intertemporal Budget Constraint

Abstract: We analyze the sustainability of the government's intertemporal budget constraint and the corresponding fiscal reaction function within a nonlinear error‐correction framework. Our empirical analysis, based on Italy, provides some evidence that the Italian government is meeting its intertemporal budget constraint. Nevertheless, we show that the burden of correcting budgetary disequilibria is entirely carried out by changes in the average tax rate, with a weakly exogenous government spending, possibly determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
(70 reference statements)
1
20
0
2
Order By: Relevance
“…Additional evidence on nonlinear fiscal adjustments over the U.S. fiscal history is provided by Sarno (2001), Arestis, Cipollini and Fattouh (2004), and Cipollini, Fattouh and Mouratidis (2009). Such a type of 'delayed' budgetary policy measures when debt tends to accumulate overtime is also detected for the historical fiscal record in the U.K since 1919 (Considine and Gallagher, 2008;Arghyrou and Fan, 2013) and for European countries historically subject to fiscal imbalances-such as Italy, Spain, Portugal, Ireland and Greece (Bajo-Rubio, Esteve, 2004, 2006;Arghyrou and Luintel, 2007;Legrenzi and Milas, 2012a, 2012bPiergallini and Postigliola, 2013). Postponed corrective actions in the conduct of fiscal policy are further shown to have occurred in Latin American and Caribbean countries (Chortareas, Kapetanios and Uctum, 2008).…”
Section: Related Literature and Model Choicementioning
confidence: 96%
“…Additional evidence on nonlinear fiscal adjustments over the U.S. fiscal history is provided by Sarno (2001), Arestis, Cipollini and Fattouh (2004), and Cipollini, Fattouh and Mouratidis (2009). Such a type of 'delayed' budgetary policy measures when debt tends to accumulate overtime is also detected for the historical fiscal record in the U.K since 1919 (Considine and Gallagher, 2008;Arghyrou and Fan, 2013) and for European countries historically subject to fiscal imbalances-such as Italy, Spain, Portugal, Ireland and Greece (Bajo-Rubio, Esteve, 2004, 2006;Arghyrou and Luintel, 2007;Legrenzi and Milas, 2012a, 2012bPiergallini and Postigliola, 2013). Postponed corrective actions in the conduct of fiscal policy are further shown to have occurred in Latin American and Caribbean countries (Chortareas, Kapetanios and Uctum, 2008).…”
Section: Related Literature and Model Choicementioning
confidence: 96%
“…For Italy, Arghyrou and Luintel (2007) …nd evidence of non-linear …scal adjustments of revenues to expenditures from 1957 to 1998; Ricciuti (2008) …nds that taxes and spending display non-linear trend stationarity from 1862 to 1998, and further they non-linearly co-trend; Legrenzi and Milas (2012b) show the occurrence of sustainable non-linear tax increases with no evidence for spending corrections from 1960 to 2008; Legrenzi and Milas (2012a) examine the stochastic properties of the debt-GDP ratio series and detect non-linear mean reversion from 1861 to 2010. This paper makes use of the Italy's overall historical …scal record to assess the empirical performance of feedback budgetary policies, that allow for possible tax-smoothing objectives (Barro, 1979(Barro, , 1986, and explicitly react to debt (Bohn 1998(Bohn , 2008 in a non-linear way.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Papadopoulos and Sidiropoulos (1999), De Castro and Hernandez de Cos (2002), Trachanas & Katrakilidis (2013), Arghyron and Luintel (2007), Bajo-Rubio et al (2009), and Legrenzi and Milas (2012) have found evidence that supports the existence of fiscal sustainability in countries that include Greece, Italy, and Spain. Afonso (2005) and Corsetti and Roubini (1991), on the other hand, reported results that indicate nonsustainability of the fiscal position of the countries.…”
Section: Introductionmentioning
confidence: 99%